Implementasi Pembelajaran Berdiferensiasi pada Mata Pelajaran PPKn dalam Mewujudkan Merdeka Belajar di SMP Labschool Jakarta - Abhi Rachma Ramadhan; Afif Afif; Annisa Chaerani; Hazmin Hafid Putranto (Ideas Publishing, 2023)
The low fulfillment of learning needs is an obstacle for students, in addition to the use of a curriculum that is still a rote system, and a lack of diverse values results in students being passive in the teaching and learning process. As students have characteristics that must be met, one of the diverse lessons is Civics. This study aims to see the results of differentiated learning in the implementation of the independent curriculum in Civics subjects held in class IX-A at SMP Labschool Jakarta as the subject of the research. Then the approach taken is qualitatively using a descriptive analysis method which is carried out in two parts, namely activity analysis and other files. The results obtained are differentiated learning that is suitable for practice in the classroom environment at school as part of the need for learning in Civics lessons. So, it is hoped that students can develop their learning activities optimally. This can be seen in the evaluation section, which shows the diversity that exists within each student.